2018
DOI: 10.1186/s12934-018-0941-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an improved Aspergillus niger platform for enhanced glucoamylase secretion

Abstract: BackgroundThe lifestyle of filamentous fungi depends on the secretion of hydrolytic enzymes into the surrounding medium, which degrade polymeric substances into monomers that are then taken up to sustain metabolism. This feature has been exploited in biotechnology to establish platform strains with high secretory capacity including Aspergillus niger. The accepted paradigm is that proteins become mainly secreted at the tips of fungal hyphae. However, it is still a matter of debate if the amount of growing hypha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 47 publications
(72 reference statements)
1
41
0
Order By: Relevance
“…The A. niger hyperbranching strain MF22.4, which has been shown to be a better protein‐secretion strain than the wild‐type strain (due to deletion of the racA gene; Fiedler, Barthel, Kubisch, Nai, & Meyer, ), was used in this study. Pellets were obtained by submerged cultivation of MF22.4 for 48 hr and freeze‐drying following the previously described protocol (Schmideder et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The A. niger hyperbranching strain MF22.4, which has been shown to be a better protein‐secretion strain than the wild‐type strain (due to deletion of the racA gene; Fiedler, Barthel, Kubisch, Nai, & Meyer, ), was used in this study. Pellets were obtained by submerged cultivation of MF22.4 for 48 hr and freeze‐drying following the previously described protocol (Schmideder et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In A. niger, the Rho GTPase RacA regulates the polymerization and depolymerization of actin at the tip of mycelium (Kwon et al, 2011). When racA was deleted, the mycelial tip increased by about 20%, the number of secreted vesicles increased, and the secretion of glucoamylase increased 4 times as compared to the wild type strain (Fiedler et al, 2018). Similarly, deletion of racA resulted in a hyperbranched phenotype and three folds increase of cellulase activity in T. reesei (Fitz et al, 2019).…”
Section: Regulation Of Mycelium Morphologymentioning
confidence: 99%
“…Xin et al [21] also demonstrated that overexpression of glucoamylase encoding gene glaA and α-amylase encoding gene amyA substantially increases the expression and secretion of glucoamylase in A. niger. Furthermore, researchers were also focused on the improvement of protein secretion ability to increase glucoamylase production [22,23]. However, introduction of excessive glaA copies may overload host cells and fails to increase glucoamylase production.…”
Section: Open Accessmentioning
confidence: 99%